Managing difficult interactions expert solutions to everyday challenges. (Pocket mentor series., 2008)
In the business world, confrontations are inevitable-whether they're with your employees, peers, bosses, or even suppliers and customers. Ignored or handled badly, confrontations can damage workplace relationships and ruin careers. (Barnes & Noble)